PENGARUH BELANJA DAERAH, PENDAPATAN ASLI DAERAH (PAD), DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI PROVINSI JAWA TIMUR TAHUN 2018–2023 - Putra, Muhammad Yusuf Sunaryo; Sukartini, Ni Made (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effect of Regional Expenditure, Local Own-Source Revenue, and Investment on Economic Growth in East Java Province during 2018–2023. This research used a quantitative approach with annual time series secondary data. The data were obtained from official publications of Statistics Indonesia, the Directorate General of Fiscal Balance, and the Investment Coordinating Board. The data analysis technique used multiple linear regression with SPSS, including descriptive statistics, classical assumption tests, t-test, F-test, and coefficient of determination. The results show that Regional Expenditure, Local Own-Source Revenue, and Investment partially have no significant effect on Economic Growth in East Java Province. Simultaneously, the three variables also have no significant effect on Economic Growth. However, the R-Square value of 0.550 indicates that Regional Expenditure, Local Own-Source Revenue, and Investment explain 55% of the variation in Economic Growth, while the remaining 45% is influenced by other factors outside the research model.